The Effects of Combined Abiotic and Pathogen Stress in Plants: Insights From Salinity and Pseudomonas syringae pv lachrymans Interaction in Cucumber - Chojak-Koźniewska, Joanna; Kuźniak, Elżbieta; Zimny, Janusz (Frontiers in Plant Science, 2018)
Plants are often challenged by abiotic and biotic stresses acting in combination and the response to combinatorial stress differs from that triggered by each factor individually. Although salinity and pathogens are major stressors limiting plant growth and productivity worldwide, their interaction is poorly understood. The reactions to pathogens overlap with those to abiotic stresses, and reactive oxygen species (ROS) and stress hormones represent central nodes in the interacting signaling pathways. Usually, abiotic stress negatively affects plant susceptibility to disease. Specific focus of this review is on cucumber plants exposed to salt stress and thereafter infected with Pseudomonas syringae pv lachrymans (Psl). We addressed this problem by discussing the changes in photochemistry, the antioxidant system, primary carbon metabolism, salicylic acid (SA) and abscisic acid (ABA) contents. Salt-treated plants were more prone to infection and this effect was determined by changes in the hormonal and redox balance as well as the carboxylate metabolism and activities of some NADPH-generating enzymes. Our detailed understanding of the interactive effects of biotic and abiotic stresses is fundamental to achieve enhanced tolerance to combination stress in agronomically important crops.